1988
DOI: 10.1086/165983
|View full text |Cite
|
Sign up to set email alerts
|

Ultraluminous infrared galaxies and the origin of quasars

Abstract: An evolutionary connection between ultraluminous infrared galaxies and quasars is deduced from the observations of all 10 infrared galaxies with luminosities L(8-1000 µm) ~ 10 12 L 0 , taken from a flux-limited sample of infrared bright galaxies. Images of the infrared galaxies show that nearly all are strongly interar•ing merger systems with exceptionally luminous nuclei. Millimeter-wave CO observations show that these objects typically contain 0.5-2 x 10 10 M 0 of H2. Optical spectra indicate a mixture of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

117
2,122
7
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,062 publications
(2,247 citation statements)
references
References 31 publications
117
2,122
7
1
Order By: Relevance
“…The observation that high infrared luminosity correlated with high star formation rates and major mergers led to the widely accepted evolutionary picture for extreme luminosity systems first proposed by Sanders et al (1988). A schematic diagram of this evolutionary picture is shown in Figure 2, here reproduced from Hopkins et al (2008).…”
Section: Local Infrared-luminous Galaxiesmentioning
confidence: 83%
See 1 more Smart Citation
“…The observation that high infrared luminosity correlated with high star formation rates and major mergers led to the widely accepted evolutionary picture for extreme luminosity systems first proposed by Sanders et al (1988). A schematic diagram of this evolutionary picture is shown in Figure 2, here reproduced from Hopkins et al (2008).…”
Section: Local Infrared-luminous Galaxiesmentioning
confidence: 83%
“…Kennicutt, 1998a).While 8-1000µm is inclusive of all dusty emission, the drawback is that such a wide range captures multiple types of dust emission processes, from cold diffuse dust which dominates the long-wavelength portion of the SED to hot-dust and PAH emission in the mid-infrared (described more in § 5.7) to non-star formation driven heating, like AGN heating ( § 5.6). Non-star forming processes can come close to dominating the 8-1000µm infrared luminosity, particularly for optically or X-ray identified AGN at rest-frame wavelengths < ∼ 40µm (Sanders et al, 1988;. As a result, some works have pushed a narrower range of integration limits to restrict the computation of L IR to star-formation-driven emission only.…”
Section: Estimating L Ir T Dust and M Dust From An Sedmentioning
confidence: 99%
“…Sanders et al 1988;Treister et al 2012;Bessiere et al 2014). There is increasing evidence that most extreme local star forming galaxies, the Ultra Luminous InfraRed Galaxies (ULIRGS), are triggered by mergers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Major mergers are the mergers of two disc galaxies of comparable mass, using the numerical simulations, Mihos & Hernquist (1996) have shown that starburst activities during the merger process could be two orders of magnitude higher than that in isolated galaxies and can be sustained from several 10 7 yr to ∼ 2 × 10 8 yr after the collision. It could be the case of many infrared luminous galaxies, which are found to show morphological peculiarities indicative of encounters, such as multiple nuclei, tidal tails, loops, and shells (Sanders et al 1988;Sanders 1992). Though major mergers trigger the most powerful starburst, they are less common than minor mergers with the satellite less than 10% of the galaxy's mass.…”
Section: Discussionmentioning
confidence: 99%